Safety of gold nanoparticles: a preliminary in vitro and in vivo toxicity assessment - Silvério, Inês Torres Pereira (2021)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, 2021, Universidade de Lisboa, Faculdade de Farmácia.